Sucrosomial® iron effectiveness in recovering from mild and moderate iron-deficiency anemia in the postpartum period - Edu Antoine; Claudia Mehedintu; Mihai Mitran; Doru Diculescu (BMC, 2023)
Abstract Background Postpartum iron deficiency anemia (PPIDA) is highly prevalent in developing countries where it constitutes an important cause of maternal morbidity and mortality. Potential determinants of PPIDA are prepartum iron deficiency or iron deficiency anemia in association with severe blood loss during delivery. We investigated the efficacy of oral Sucrosomial® iron for recover from mild-to-moderate PPIDA. Methods This pilot study was conducted in three medical centers in Romania. Adult women (≥ 18y) with mild (hemoglobin [Hb] 9-11 g/dL) or moderate (Hb 7-9 g/dL) PPIDA diagnosed at screening (2-24 h after delivery) were eligible. Women with mild PPIDA received oral Sucrosomial® iron (Pharmanutra, S.p.A, Italy) once daily (30 mg elemental iron per capsule) for 60 days. Those with moderate PPIDA received oral Sucrosomial® iron twice daily (60 mg elemental iron) for 10 days, followed by a 50-day course of oral Sucrosomial® iron once daily (30 mg elemental iron). Laboratory parameters, as well as subjective clinical symptoms using a 3-point Likert Scale, were assessed at baseline and on study days 10, 30 and 60. Results Sixty anemic women entered the study, but three were missed during follow-up. At day 60, a Hb rise was observed in both groups (+ 3.6 ± 1.5 g/dL; p < 0.01), 81% experienced correction of anemia (Hb ≥ 12 g/dL), 36% achieved a ferritin concentration ≥ 30 ng/mL (p < 0.05), and 54% a transferrin saturation (TSAT) ≥ 20% (p < 0.01). For women still anemic at day 60, mean Hb was close to normality (11.3 ± 0.8 g/dL). Resolution of IDA-associated clinical symptoms was already observed just 10 days after treatment initiation. No patient discontinued treatment due to gastrointestinal adverse events. Conclusions Sucrosomial® iron was shown to be potentially effective and well tolerated at treating mild and moderate PPIDA. These results encourage the use of oral Sucrosomial® iron as a treatment option for PPIDA, but larger studies with longer follow-up are warrant.